The Post-Buckling Behaviour of Thin-Walled Columns in the Elasto-Plastic Range - Kowal-Michalska, K.; Grądzki, R. (Engineering Transactions, 1986)
The post-buckling behaviour in the elasto-plastic range of thin-walled, steel columns subject to uniform compression is analysed. The problem is solved using the Rayleigh-Ritz variational method involving plasticity. The plastic stress-strain relations are described by Prandtl-Reuss equations. Numerical calculations have been carried out for different geometrical parameters and material properties. The load-shortening curves and the spreads of plasticity regions in component plates of a column are presented in figures.